Freshwater salinisation: a research agenda for a saltier world. (May 2022) - Cunillera-Montcusí, David; Beklioğlu, Meryem; Cañedo-Argüelles, Miguel; Jeppesen, Erik; Ptacnik, Robert; Amorim, Cihelio A.; Arnott, Shelley E.; Berger, Stella A.; Brucet, Sandra; Dugan, Hilary A.; Gerhard, Miriam; Horváth, Zsófia; et al.
Abstract : The widespread salinisation of freshwater ecosystems poses a major threat to the biodiversity, functioning, and services that they provide. Human activities promote freshwater salinisation through multiple drivers (e.g., agriculture, resource extraction, urbanisation) that are amplified by climate change. Due to its complexity, we are still far from fully understanding the ecological and evolutionary consequences of freshwater salinisation. Here, we assess current research gaps and present a research agenda to guide future studies. We identified different gaps in taxonomic groups, levels of biological organisation, and geographic regions. We suggest focusing on global- and landscape-scale processes, functional approaches, genetic and molecular levels, and eco-evolutionary dynamics as key future avenues to predict the consequences of freshwater salinisation for ecosystems and human societies. Highlights: The global acceleration of freshwater salinisation due to human activities such as agriculture, resource extraction, and urbanisation and its amplification by climate change is unequivocal. Although research in this field is growing, there are key aspects at the ecological and evolutionary levels that remain unaddressed. Increasing salinisation is a problem as it can increase the stress or mortality of freshwater organisms, leading to a loss of diversity and/or functionality of freshwater ecosystems but also the services and benefits to human societies that they provide. We identify the main gaps of recent research and suggest a research agenda to facilitate future research efforts in order to achieve a more comprehensive understanding on freshwater salinisation.